Intelligent matter endows reconfigurable temperature and humidity sensations for in-sensor computing. Issue 3 (24th January 2023) - Guo, Tao; Ge, Jiawei; Jiao, Yixuan; Teng, Youchao; Sun, Bai; Huang, Wen; Asgarimoghaddam, Hatameh; Musselman, Kevin P.; Fang, Yin; Zhou, Y. Norman; Wu, Yimin A.
Abstract : Intelligent matter with smart responses to environmental stimulation paves the way to implement data-centric tactics with in-sensor computing, which bypasses redundant data shuttling. Abstract : Data-centric tactics with in-sensor computing go beyond the conventional computing-centric tactic that is suffering from processing latency and excessive energy consumption. The multifunctional intelligent matter with dynamic smart responses to environmental variations paves the way to implement data-centric tactics with high computing efficiency. However, intelligent matter with humidity and temperature sensitivity has not been reported. In this work, a design is demonstrated based on a single memristive device to achieve reconfigurable temperature and humidity sensations. Opposite temperature sensations at the low resistance state (LRS) and high resistance state (HRS) were observed for low-level sensory data processing. Integrated devices mimicking intelligent electronic skin (e-skin) can work in three modes to adapt to different scenarios. Additionally, the device acts as a humidity-sensory artificial synapse that can implement high-level cognitive in-sensor computing. The intelligent matter with reconfigurable temperature and humidity sensations is promising for energy-efficient artificial intelligence (AI) systems.